2015
DOI: 10.1371/journal.pone.0144104
|View full text |Cite
|
Sign up to set email alerts
|

The High Prevalence of Low HDL-Cholesterol Levels and Dyslipidemia in Rural Populations in Northwestern China

Abstract: BackgroundDyslipidemia is a major health problem in China and an important modifiable cardiovascular disease (CVD) risk factor. This study aimed to describe the prevalence of dyslipidemia and low high density lipoprotein cholesterol (HDL-cholesterol) and associated risk factors among adults in rural northwest China.MethodsIn a cross-sectional analyses involving 2,980 adults aged >18 years, information on the demographics, cigarette smoking, alcohol consumption, education, and medical history was collected via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 27 publications
4
27
0
1
Order By: Relevance
“…One study showed that anthropometric measurements can be used as practical tools for assessing metabolic risk in overweight‐obese people . And a compelling body of studies demonstrated that obesity is an important risk factor for dyslipidaemia . Body mass index and waist circumference (WC) are considered practical and effective indexes to evaluate obesity .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study showed that anthropometric measurements can be used as practical tools for assessing metabolic risk in overweight‐obese people . And a compelling body of studies demonstrated that obesity is an important risk factor for dyslipidaemia . Body mass index and waist circumference (WC) are considered practical and effective indexes to evaluate obesity .…”
Section: Introductionmentioning
confidence: 99%
“…5 And a compelling body of studies demonstrated that obesity is an important risk factor for dyslipidaemia. [6][7][8] Body mass index and waist circumference (WC) are considered practical and effective indexes to evaluate obesity. 9 Body mass index is closely related to body fat 10,11 but cannot accurately reflect the distribution of fat mass in the body.…”
Section: Introductionmentioning
confidence: 99%
“…This study also showed that high total cholesterol level and low HDL were predictors of obesity (Table 4). A chinese study supports that low HDL was associated with obesity and overweight (BMI) and the association was stronger with central obesity using waist circumference (p<0.001) (35). Respondents with high total cholesterol levels were 1.5 times more likely to be obese compared to those with normal or low total cholesterol level (OR 1.54, 95% CI 0.441-5.386, p-0.264).…”
Section: Discussionmentioning
confidence: 81%
“…Obesity results from complex interaction of genetic, lifestyle, dietary habits, energy expenditure, nutritional and metabolic factors as the adipocyte metabolism [15] [16]. Fat accumulation and location constitute risk factors for diabetes, cardiovascular diseases [2] and dyslipidemia [17]. Dyslipidemia is a condition of an abnormal lipid or lipoprotein concentration in the blood.…”
Section: Introductionmentioning
confidence: 99%